Qualidade Vida no Teletrabalho: um estudo de caso no Tribunal de Justiça do Estado de Minas Gerais - Erlando Bruno Bessa Júnior (2022)
Quality of life at Work (QWL) is important because it is related to the well-being and health of people. In the context of Quality of Life of Telework (QTL), it is a theme still little explored, because, although telecommuting has existed for decades, it is in recent years that it has taken more significant contours. This research consists of a case study that sought to analyze the perceptions of first instance public servant of the Court of Justice of Minas Gerais in relation to Quality of Life at Telework. The interviews conducted with thirteen judicial officers of the first instance were submitted to content analysis, whose categories were based on the five structuring factors of Quality of Life at Work, according to the theoretical methodological model of Ergonomics of Activity Applied to Quality of Life at Work (EAA_QVT), proposed by (FERREIRA, 2012). As a main finding, it has that the perceptions of the participants are predominantly positive regarding the telework regime in TJMG, and therefore, there is QTL. The interpretation of the data also showed that the main positive perceptions are due, above all, to the flexibility of the work schedule, proximity to the family, autonomy to organize and perform the work, use of communication tools, reduced commuting, greater ability to concentrate, reconciliation between work and personal life, greater autonomy and flexibility to organize their own routine, higher productivity and quality of work. The main negative perceptions reveal concerns related, especially, to slowness and problems in the systems, social and professional isolation, socio-professional conflicts, difficulties between work/life balance. This study made theoretical, methodological and managerial contributions by deepening the investigation about quality of life in telework, bringing the worker to the center of the discussion. It alerts to the need to rethink work processes, which have been moving towards a loss of social relationship factors, leaving only technical and professional aspects. It proposes to question the technological innovations as something inexorable that must advance at any cost and also makes other provocations, discussing the results in the light of a vision that opposes the assistentialist concept, from a preventive, multidisciplinary and health promotion perspective.